IMPACT OF COMPRESSIONAL STRESSES WITHIN THE SOUTH CASPIAN MEGADEPRESSION UPON EVOLUTION AND OIL AND GAS CONTENT OF LOCAL UPLIFTS - Gurbanov, V.; Narimanov, N.; Nasibova, G. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The following structural elements in the South Caspian megadepression (SCMD) have been considered: the interfluve of the Kura and Gabirri, the Absheron and Baku archipelagoes, the Lower Kur depression (LKD) and the Godin massif, that stand out geodynamically, from point of view of structural and tectonic evolution and oil and gas content. To solve this problem, the geodynamic environment of the SCMD has been analyzed based on the geodynamic chart of the Central segment of the Mediterranean folding belt compiled by the author, as well as the orientation chart of compressional stresses in the SCD and the methodology, developed for the first time ever, for their qualitative assessment within the structural elements by means of compiling isomorphic maps. The latter make it possible to determine the intensity and nature of the propagation of compressional stresses, the specifics of their impact on folding, oil and gas generation and formation of hydrocarbon accumulations. The Kur-Gabirri interfluve is situated in the west of the SCMD between the closely located Greater and Lesser Caucasian collisions. It is characterized by oil and gas bearing and potential sublatitudinally oriented linear folds, complicated by faulting and mud volcanism. The values of isolines of the isomorphic map and their density are indicative of high intensity of the north-west oriented compressional stresses here. The Absheron archipelago is a western element of the Absheron-Balkhan residual subduction. According to the isomorphic map with a dense network of isolines of sublatitudinal orientation, the archipelago is complicated by linear folding, as well as thrusts, transverse strike-slip faults, mud volcanism, oil and gas content, and oil and gas manifestations indicating the build-up of intense compressional stresses here. Evolution of folds within the Baku archipelago and the Lower Kur depression took place under the stresses of longitudinal and transverse bending. The faintly pronounced linearity of the compressional stresses is apparently associated with the formation of the Western Board of the SCD in the form of a regional submeridianal uplift. It developed under the impact of compressional stresses arising from the effect of the northeastern projection of the Arabian plate on the Iranian one. LKD is an onshore extension of the Baku archipelago. Its anticline zones, regional faults, mud volcanism and oil and gas content continue in the latter. The Godin Massif is the easternmost structural element of those considered with a faintly pronounced reflected folding of unknown prospects. Isolines of the isomorphic map are not directly associated with local uplifts, which is indicative of the absence of clearly pronounced compressional stresses here. The analysis made it possible to determine the degree of development of compressional stresses, their impact upon formation of the sedimentary section, folding, mud volcanism and oil and gas content of the considered structural elements.